Home-based respiratory rehabilitation in adult patients with moderate or severe persistent asthma. (June 2014) - Renolleau-Courtois, Delphine; Lamouroux-Delay, Aurore; Delpierre, Stéphane; Badier, Monique; Lagier-Tessonnier, Françoise; Palot, Alain; Gouitaa, Marion; Tummino, Céline; Charpin, Denis; Molinari, Nicolas; Chanez, Pascal
Abstract Objective: We assessed retrospectively the feasibility of a home-based respiratory rehabilitation (RR) program for asthmatics under optimal pharmacological treatment, as this type of care can reduce costs and offer a more patient-friendly approach for subjects with persistent asthma. Methods: Fifty-two patients with persistent asthma were recruited to the RR program (20 males, 32 females, 54 ± 11 (SD) years, forced expiratory volume in one second 71 ± 33% of predicted mean value, BMI 29.9 ± 7.9 kg/m2). This two-month protocol comprised education sessions, respiratory physiotherapy and an exercise training program at home and in groups supervised by an adapted physical activity instructor. Results: Thirty-nine patients completed the whole RR program, i.e. 25% dropout. The dropout rate was significantly higher with respect to younger patients in employment. The number of exacerbations decreased significantly during the year following the program, regardless of whether the patients had dropped out (p < 0.02) or not (p < 0.001). The distance walked during a 6-min walking test increased by 33 m (p < 0.001). Several indices measured during a cycle ergometer test increased significantly after RR: peak oxygen uptake (10%), oxygen uptake at ventilatory threshold (12%) and maximum load (19%), all at a similar maximum heart rate. Concerning quality of life assessment, the Short-Form-36 Item Health Survey revealed a non-significant improvement in the "health change" item after RR (p < 0.07). Conclusions: This study demonstrates the potential of a home-based program in the treatment and rehabilitation of patients with asthma. Both functional and physiologic indices improved during the follow-up period.